THE TALIBAN WAR ON WOMEN’S EDUCATION A HUMAN RIGHT CRISES IN AFGHANISTAN - Imad Hilal (International Journal of Contemporary Issues in Social Sciences, 2024)
Approximately 80% of school-aged Afghan girls and young women being out of school, with nearly 30% having never entered primary education under the Taliban’s interpretation of Sharia Law in Afghanistan. This research paper examines the critical issue of the ban on women and girls’ education in Afghanistan by the Taliban, analyzed through International Human Rights Law (IHRL) and Sharia law. It questions the disparity between the right to education for women under IHRL and their rights under the Taliban’s interpretation of Sharia Law in Afghanistan. The paper uses doctrinal research methods to assess how the rights to education under IHRL align or conflict with those granted to women in Afghanistan under the Taliban’s version of Sharia. Both legal frameworks recognize education as a fundamental human right, yet the Taliban’s ban clearly violates these principles. The study details the main sources of Sharia law, such as the Quran and Hadiths, which universally advocate the pursuit of knowledge and mandate that parents provide their children with a proper education. It argues that the Taliban’s interpretation of these texts is not only incorrect but also manipulated to advance the regime’s specific agendas, rather than reflecting the true spirit of Islamic teachings. Additionally, the paper discusses international legal standards that protect educational rights, citing key documents like the Universal Declaration of Human Rights (UDHR), the Convention on the Elimination of All Forms of Discrimination Against, Women (CEDAW), and the International Covenant on Economic, Social, and Cultural Rights (ICESCR). It firmly concludes that the Taliban’s educational ban is a clear violation of International Human Rights Law. The study also highlights the non-discriminatory nature of educational rights under both IHRL and Islamic law, stating that any denial of such fundamental rights is a serious violation punishable under both legal systems. It refutes any perceived differences between the rights of education for women under IHRL and under Taliban’s Sharia, affirming that both doctrines fundamentally support equal educational opportunities for women. Based on these findings, the paper proposes several actionable recommendations to reverse the educational ban. It suggests that the international community increase pressure on the Taliban through diplomatic channels, economic sanctions, and support for women’s rights advocates. It also calls on Muslim-majority countries to use their cultural and religious influence to advocate for the restoration of women’s educational rights in Afghanistan. The role of human rights activists in promoting this issue globally is emphasized, advocating for a strong campaign across social media and through public demonstrations to raise awareness and spur international and grassroots action against the education ban. In summary, this comprehensive legal analysis exposes the educational ban in Taliban-administered Afghanistan as a breach of universally recognized human rights laws and a distortion of Islamic legal principles. The paper not only clarifies the legal discrepancies but also offers a strategic framework for international and local stakeholders to work together to restore educational rights for Afghan women and girls.